Implementasi Pembelajaran Online pada Sekolah Dasar Negeri di Daerah Pinggiran Perkotaan - Sakti, Bayu Purbha; Ayu, Risma Eka (Musamus Journal of Primary Education, 2021)
This research is caused by online learning conducted by public elementary school in suburban areas. Online learning is carried out because the â€œCovid-19â€ virus outbreak has become a disaster in the world of education. Online learning requires several facilities such as an internet signal and a smartphone. This facility becomes a problem if an area experiences internet problems. This research is a qualitative descriptive study of phenomenology. The subjects in this study were teachers, parents, and fourth grade students. Data collection used is interviews, observation, and documentation. The data analysis used was data reduction, data presentation and conclusion drawing.The results of this study indicate that the implementation of online learning in grade IV public elementary school in suburban areas during the â€œCovid-19â€ pandemic was shown based on input, process, and output indicators. This can be seen from the input indicator, namely the application of teacher characteristics, namely motivation, fostering enthusiasm, and mastering technology, communication. The learning facilities used by students include cellphones/smartphones, internet networks, and the cost of buying internet data packages. Process indicators are related to the allocation of teacher time, namely managing time effectively. The application of time allocation for students is to take advantage of time tolerance in completing tasks. The output indicator is related to student learning outcomes. The application of changes in student attitudes is to be more motivating, disciplining, and timely in submitting assignments.